The Effect of Using Quizizz Learning Media to Improve Student Learning Outcomes in Science in Grade V SDN 2 Sindue Tobata - Zain Rahmat Mudzakir; Sinta Satria Dewi Pendit; Sisriawan Lapasere; Abdul Rahman; Putriwanti Putriwanti (FKIP - Universitas Riau, 2026)
The integration of digital learning media has become an important strategy for improving student engagement and learning outcomes in elementary education. However, the use of game-based learning platforms such as Quizizz remains limited in elementary science classrooms. This study aimed to examine the effect of Quizizz learning media on the science learning outcomes of fifth-grade students at SDN 2 Sindue Tobata. A quantitative pre-experimental approach using a One Group Pretest–Posttest Design was employed. The participants consisted of 20 fifth-grade students selected through saturated sampling. Data were collected using validated achievement tests and analyzed through descriptive statistics, the Shapiro–Wilk normality test, the Paired Sample t-test, and the normalized gain (N-Gain) test. The findings indicate that Quizizz significantly improved students' science learning outcomes while increasing their motivation, participation, and engagement during classroom activities. The learning improvement reached a moderate level of effectiveness, demonstrating that Quizizz is an effective digital learning medium. This study provides empirical evidence supporting the integration of game-based learning media to promote student-centered science learning in elementary schools.